1996
DOI: 10.1557/proc-445-229
|View full text |Cite
|
Sign up to set email alerts
|

Composite Materials with Adjustable Thermal Expansion for Electronic Applications

Abstract: In this paper, we discuss a newly characterized compound, ZrW2Og, that has been introduced into the composite materials with an adjustable and low thermal expansion for electronic applications. Offering a negative coefficient of thermal expansion (CTE) of approximate ‐9xlO–6/°C in a large temperature range, ZrW2Og was used as a particle filler in polymer‐matrix composites. The paper presents two kinds of composites, that is, polyester and epoxy with various volume fractions of ZrW20g. The CTEs of the polyester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…However, in some cases, such as Al 2 TiO 5 , microstructural design and microcrack formation can be used to advantage to produce low thermal expansion materials with high thermal shock resistance [10]. On the other hand, the second approach makes use of the addition of thermomiotics, as the dispersed phase, in composites [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The most common role of thermomiotics in composites is to control the CTE of the matrix phase, which could be a metal, ceramic or polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases, such as Al 2 TiO 5 , microstructural design and microcrack formation can be used to advantage to produce low thermal expansion materials with high thermal shock resistance [10]. On the other hand, the second approach makes use of the addition of thermomiotics, as the dispersed phase, in composites [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The most common role of thermomiotics in composites is to control the CTE of the matrix phase, which could be a metal, ceramic or polymer.…”
Section: Introductionmentioning
confidence: 99%
“…These tentative attempts generally focus on ZrW 2 O 8 , both as micronic and nanometric powders [11,[15][16][17][23][24][25]. This is understandable considering the isotropic physical properties of ZrW 2 O 8 and its strong negative CTE (* -9 9 10 -6 K -1 ) over a wide temperature range (0-1050 K), which includes the operational temperature range for polymer components.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al first reported that cubic zirconium tungstate (ZrW 2 O 8 ), which exhibits large negative CTE at 8.7 ppm/K [4], can be used to reduce the thermal expansion of polyester and epoxy resin in 1997 [5]. Loadings of ZrW 2 O 8 particles ranging from 0 to 30 vol % significantly reduce the CTEs from 94 to 56 ppm/K for polyester and from 54 to 18 ppm/K for epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Despite its large negative CTE and interesting phase behavior, only a few researchers have examined the impact of ZrW 2 O 8 as filler in polymer matrix composites. Shi and coworkers 10 reported that the incorporation of 30 volume (vol)% of ZrW 2 O 8 with a polyester resin resulted in a 40% decrease in CTE. Weyer and coworkers 11 observed an 80% reduction in CTE on addition of up to 52 vol% ZrW 2 O 8 in a cyanate ester resin.…”
Section: Introductionmentioning
confidence: 99%